1997
DOI: 10.1021/bi971550l
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the pH Dependence of Inhibitor Binding Energetics for an Aspartic Protease:  Direct Measurement of the Protonation States of the Catalytic Aspartic Acid Residues,

Abstract: The catalytic activity and inhibitor binding energetics of enzymes are often pH-dependent properties. Aspartic proteases comprise an important class of enzyme targets for structure-based drug design. We have performed a complete thermodynamic study of pepstatin binding to plasmepsin II, an aspartic proteinase found in Plasmodium falciparum, using isothermal titration calorimetry and circular dichroism. Thermodynamic parameters (DeltaG, DeltaH, DeltaCp, and DeltaS) were measured as functions of both pH and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 34 publications
6
73
0
2
Order By: Relevance
“…Multifunctional catalysis is based on simultaneous effects of nucleophylic and electrophylic groups of the enzyme catalytic site on the carbonyl group of the peptide bond. Attachment of the substrate is followed by two synchronized transfer reactions: in the first, the proton is transferred from a water molecule onto a carboxyl anion of Asp33, in the other, the proton derived from a carboxyl group of Asp231 is transferred onto the oxygen of the carbonyl group of the substrate, giving rise to a tetraedric intermediate [81][82][83][84][85][86].…”
Section: Mechanismmentioning
confidence: 99%
“…Multifunctional catalysis is based on simultaneous effects of nucleophylic and electrophylic groups of the enzyme catalytic site on the carbonyl group of the peptide bond. Attachment of the substrate is followed by two synchronized transfer reactions: in the first, the proton is transferred from a water molecule onto a carboxyl anion of Asp33, in the other, the proton derived from a carboxyl group of Asp231 is transferred onto the oxygen of the carbonyl group of the substrate, giving rise to a tetraedric intermediate [81][82][83][84][85][86].…”
Section: Mechanismmentioning
confidence: 99%
“…This finding is consistent with the data acquired from the crystallographic study [5] which showed that the interaction between native SFTI-1 and trypsin is stabilized by an extensive network of hydrogen . This approach has been applied earlier to several protein systems including aspartic protease [21], stromelysin-1 [22] and HIV-1 protease [23] to dissect protonation contributions from binding. The enthalpy measured in the ITC experiment, D ITC H, is the sum of all energetic effects accompanying the reaction, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…for elastase, endothiapepsin, and plasmepsin II. 10,[43][44][45] Nevertheless, the present system experiences solubility limitations that restrict the required broad range pH variations. Furthermore, significant pH changes will likely alter the protonation states of other protein and ligand titratable groups, along with their ionization enthalpies in the bound and unbound state.…”
Section: Discussionmentioning
confidence: 99%